2013
DOI: 10.1177/1479164113482694
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated health predicts outcome in patients with type 2 diabetes and myocardial infarction: A DIGAMI 2 quality of life sub-study

Abstract: The Diabetes mellitus Insulin-Glucose Infusion in Acute Myocardial Infarction (DIGAMI) 2 Quality of Life (QoL) sub-study included 465 patients with type 2 diabetes and acute myocardial infarction (AMI) followed for 2 years. Self-rated health was reported by the rating scale (RS), graded 0 = death to 100 = perfect health. Prospective associations between RS and all-cause mortality, cardiovascular (CV) death and cardiovascular events (CVEs = CV death, non-fatal AMI, stroke) were assessed. Median age was 68 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Quality of life (QoL) measures are frequently utilized tools for outcomes analysis post-stroke, but may also serve as an important independent predictor of major diseases. Health-related QoL has been reported to independently predict mortality following Coronary Artery Bypass Grafting (CABG) 3 , Myocardial Infarction (MI) 4,5 , heart failure 6 , Diabetes Mellitus 78 , and Hemodialysis 9 . Egido et al found that psychosocial stress predicted stroke in a small case-control study, implying that QoL is a significant causative role 1011 .…”
Section: Introductionmentioning
confidence: 99%
“…Quality of life (QoL) measures are frequently utilized tools for outcomes analysis post-stroke, but may also serve as an important independent predictor of major diseases. Health-related QoL has been reported to independently predict mortality following Coronary Artery Bypass Grafting (CABG) 3 , Myocardial Infarction (MI) 4,5 , heart failure 6 , Diabetes Mellitus 78 , and Hemodialysis 9 . Egido et al found that psychosocial stress predicted stroke in a small case-control study, implying that QoL is a significant causative role 1011 .…”
Section: Introductionmentioning
confidence: 99%
“…According to the GRACE score, the median (interquartile range [IQR]) risk of post-discharge death in the next 6 months was 5%. [3][4][5][6][7][8][9] Per study design, the average level of perceived acute distress during MI was substantial, whereas the average level of cognitive depressive symptoms was low.…”
Section: Resultsmentioning
confidence: 96%
“…Low self-rated health (SRH), assessed with a single-item question, is a robust predictor of all-cause mortality over a follow-up of 1 to 25 years 1 and of cardiovascular mortality in individuals with and without cardiovascular disease (CVD) after 2 to 23 years of follow-up. 2 In patients with coronary heart disease, SRH predicted recurrent coronary events and death, 3 as well as all-cause mortality, death from CVD, nonfatal myocardial infarction (MI) and stroke, 4 all after 2 years of follow-up. When assessed within a few days after acute coronary syndrome (ACS), SRH predicted mortality at 1-year follow-up, 5 whereas improvement in SRH from 1 year before to 3 to 6 months after MI lowered the risk of recurrent cardiac ischemic events during 13 years of follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…The impact that these generate in the physical, mental and social well-being of individuals, being important in the analysis of individual and population health by health professionals. (11) Understanding the health subjectively creates relationships with other factors involving the individual's life (such as access to information), in addition to the physical condition, which reinforces its importance as an indicator of health needs.…”
Section: Discussionmentioning
confidence: 99%